Exploring the relationship between reverse logistics and sustainability performance: A literature review - Taknaz Alsadat Banihashemi; Jiangang Fei; Peggy Shu-Ling Chen (Modern Supply Chain Research and Applications, 2019)
Purpose – The implementation of reverse logistics (RL) as a strategic decision has gained significant attention amongst organisations due to its benefits to sustainable development. The purpose of this paper is to provide a comprehensive review of the literature to evaluate the performance of the RL process based on the three dimensions of sustainability including environmental, economic and social aspects. Design/methodology/approach – Content analysis was adopted to collect and analyse the information. Findings – The findings of this research show that most of the studies have focused on the performance evaluation of RL by considering the factors associated with economic and environmental performance. The social aspect of RL has been overlooked and requires investigation due to its contribution to positive social outcomes. In addition, no research has been conducted to assess the impact of each of the disposition options on the triple-bottom-line sustainability performance in one study. Originality/value – Although RL can make a significant contribution to improving the sustainability performance of firms, little research has been undertaken on exploring the relationship between RL and sustainability performance. This paper provides practitioners, academics and researchers a broad and complete view of the relationship between RL and sustainability performance with suggestion for future research.